Peripheral B Cell Deficiency and Predisposition to Viral Infections: The Paradigm of Immune Deficiencies - Grammatikos, Alexandros; Donati, Matthew; Johnston, Sarah L.; Gompels, Mark M. (Frontiers in immunology, 2021)
In the era of COVID-19, understanding how our immune system responds to viral infections is more pertinent than ever. Immunodeficiencies with very low or absent B cells offer a valuable model to study the role of humoral immunity against these types of infection. This review looks at the available evidence on viral infections in patients with B cell alymphocytosis, in particular those with X-linked agammaglobulinemia (XLA), Good’s syndrome, post monoclonal-antibody therapy and certain patients with Common Variable Immune Deficiency (CVID). Viral infections are not as infrequent as previously thought in these conditions and individuals with very low circulating B cells seem to be predisposed to an adverse outcome. Particularly in the case of SARS-CoV2 infection, mounting evidence suggests that peripheral B cell alymphocytosis is linked to a poor prognosis.